Strategies to Reduce Exclusion among Populations Living in Urban Slum Settlements in Bangladesh (Journal of Health, Population and Nutrition, 2009)
The health and rights of populations living in informal or slum settlements are key development issues of the twenty-first century. As of 2007, the majority of the world's population lives in urban areas. More than one billion of these people, or one in three city-dwellers, live in inadequate housing with no or a few basic resources. In Bangladesh, urban slum settlements tend to be located in low-lying, flood-prone, poorlydrained areas, having limited formal garbage disposal and minimal access to safe water and sanitation. These areas are severely crowded, with 4-5 people living in houses of just over 100 sq feet. These conditions of high density of population and poor sanitation exacerbate the spread of diseases. People living in these areas experience social, economic and political exclusion, which bars them from society's basic resources. This paper overviews policies and actions that impact the level of exclusion of people living in urban slum settlements in Bangladesh, with a focus on improving the health and rights of the urban poor. Despite some strategies adopted to ensure better access to water and health, overall, the country does not have a comprehensive policy for urban slum residents, and the situation remains bleak. Key words: Informal settlements; Social exclusion; Slums; Slum settlements; Urban health; Bangladesh   doi: 10.3329/jhpn.v27i4.3403 J Health Popul Nutr 2009 Aug;27(4):574-586